Synthesis of a probe for monitoring HSV1-tk reporter gene expression using chemical exchange saturation transfer MRI - Bar-Shir, Amnon; Liu, Guanshu; Greenberg, Marc M; Bulte, Jeff W M; Gilad, Assaf A (Nature protocols, 2013)
In experiments involving transgenic animals or animals treated with transgenic cells, it is important to have a method to monitor the expression of the relevant genes longitudinally and noninvasively. An MRI-based reporter gene enables monitoring of gene expression in the deep tissues of living subjects. This information can be co-registered with detailed high-resolution anatomical and functional information. We describe here the synthesis of the reporter probe, 5-methyl-5,6-dihydrothymidine (5-MDHT), which can be used for imaging of the herpes simplex virus type 1 thymidine kinase (HSV1 -tk ) reporter gene expression in rodents by MRI. The protocol also includes data acquisition and data processing routines customized for chemical exchange saturation transfer (CEST) contrast mechanisms. The dihydropyrimidine 5-MDHT is synthesized through a catalytic hydrogenation of the 5,6-double bond of thymidine to yield 5,6-dihydrothymidine, which is methylated on the C-5 position of the resulting saturated pyrimidine ring. The synthesis of 5-MDHT can be completed within 5 d, and the compound is stable for more than 1 year.